2021
DOI: 10.18632/aging.203128
|View full text |Cite
|
Sign up to set email alerts
|

The dysregulated Pink1- Drosophila mitochondrial proteome is partially corrected with exercise

Abstract: One of the genes which has been linked to the onset of juvenile/early onset Parkinson's disease (PD) is PINK1. There is evidence that supports the therapeutic potential of exercise in the alleviation of PD symptoms. It is possible that exercise may enhance synaptic plasticity, protect against neuro-inflammation and modulate L-Dopa regulated signalling pathways. We explored the effects of exercise on Pink1 deficient Drosophila melanogaster which undergo neurodegeneration and muscle degeneration. We used a 'powe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…The proteomics analysis showed that exercise downregulated tropomyosin-1 isoforms 33/34, tropomyosin-2, acyl-coenzyme A dehydrogenase, isocitrate dehydrogenase, enolase, probable isocitrate dehydrogenase [NAD] subunit alpha, glycerol-3-phosphate dehydrogenase [NAD (+)], pyruvate dehydrogenase E1 component subunit beta, aldo-keto reductase isoform C, alcohol dehydrogenase, and CG9992 isoform A in PD drosophila. These molecules might be candidates to develop therapeutic approaches in PD ( Ebanks et al, 2021 ). Exercise can reverse many of the PD-related changes by downregulating the levels of hippocampal proteins functionally associated with energy metabolism (nucleoside diphosphate kinase B, enolase, and triosephosphate isomerase) and synaptic plasticity (α-synuclein, tenascin-R, Ba1-667, brevican and neurocan core protein) in the non-lesioned hemisphere of PD model rats ( Dimatelis et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…The proteomics analysis showed that exercise downregulated tropomyosin-1 isoforms 33/34, tropomyosin-2, acyl-coenzyme A dehydrogenase, isocitrate dehydrogenase, enolase, probable isocitrate dehydrogenase [NAD] subunit alpha, glycerol-3-phosphate dehydrogenase [NAD (+)], pyruvate dehydrogenase E1 component subunit beta, aldo-keto reductase isoform C, alcohol dehydrogenase, and CG9992 isoform A in PD drosophila. These molecules might be candidates to develop therapeutic approaches in PD ( Ebanks et al, 2021 ). Exercise can reverse many of the PD-related changes by downregulating the levels of hippocampal proteins functionally associated with energy metabolism (nucleoside diphosphate kinase B, enolase, and triosephosphate isomerase) and synaptic plasticity (α-synuclein, tenascin-R, Ba1-667, brevican and neurocan core protein) in the non-lesioned hemisphere of PD model rats ( Dimatelis et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…The genes being assessed are LRRK2, GBA, SNCA, PRKN, PARK 7, PINK1, and VPS35 . The potential importance of this line of research can be understood from a recent study in PINK1-deficient Drosophila melanogaster which showed that exercise caused the organism’s proteomic profile to return towards wild-type levels [ 108 ]. Future DNA analysis beyond these known PD genes in the future may help us to discern the effects of genetic risk factors for progression and response to exercise as well as potentially provide subgroup analyses based on the genetic profiles.…”
Section: Discussionmentioning
confidence: 99%